2015
DOI: 10.1371/journal.pone.0128541
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics Associated with Tuberculosis Treatment Default: A Cohort Study in a High-Incidence Area of Lima, Peru

Abstract: BackgroundAlthough tuberculosis (TB) is usually curable with antibiotics, poor adherence to medication can lead to increased transmission, drug resistance, and death. Prior research has shown several factors to be associated with poor adherence, but this problem remains a substantial barrier to global TB control. We studied patients in a high-incidence district of Lima, Peru to identify factors associated with premature termination of treatment (treatment default).MethodsWe conducted a prospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 28 publications
8
47
0
7
Order By: Relevance
“…Moreover, the available studies did not identify constraints in TB treatment as well as the timing of default. A low success rate and a high defaulting rate of 79.7% and 12.6% respectively, were reported, which is consistent with the high defaulting rates reported in similar studies, namely 7.2% in South Africa, 10% in Sudan, 17% in Busia, 10% in Lima, Peru and 9.4% in Nigeria . The importance of this study is highlighted by the fact that WHO recommends that TB defaulting rates should not exceed 10%…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the available studies did not identify constraints in TB treatment as well as the timing of default. A low success rate and a high defaulting rate of 79.7% and 12.6% respectively, were reported, which is consistent with the high defaulting rates reported in similar studies, namely 7.2% in South Africa, 10% in Sudan, 17% in Busia, 10% in Lima, Peru and 9.4% in Nigeria . The importance of this study is highlighted by the fact that WHO recommends that TB defaulting rates should not exceed 10%…”
Section: Introductionsupporting
confidence: 89%
“…The persistence of respiratory symptoms related to smoking might force the patient to stop TB treatment. Several studies have reported smoking as a risk factor of TB defaulters . However, some studies were unable to establish an association between smoking and TB treatment defaulters …”
Section: Discussionmentioning
confidence: 99%
“…Penderita TB akan mengalami penurunan nafsu makan sehingga mengalami kehilangan berat badan. Menurut penelitian Lackey (2015) responden yang kurang gizi memiliki risiko TB sebesar 2.08 kali. Hal ini disebabkan karena perubahan metabolik pada pasien TB seperti perubahan leptin darah dan penekanan eritropoesis menyebab pasien TB mengalami anemia dan malnutrisi (Lackey dkk, 2015;Nasution, 2015) Kadar Gula darah sewaktu pasien TB pada penelitian ini rata-rata 137.10 g/dl dengan kadar tertinggi adalah 178.27 g/dl, serta didapatkan 13.2% pasien TB dengan DM.…”
Section: Hasil Dan Pembahasanunclassified
“…[35] It was found that TB patients who have a problem with alcoholism do not collect their treatment regularly and were found to default treatment more than the non-alcoholic patients. [7] One health service related factor that can cause stigma is the integration of the TB and HIV departments as well as having this combined department separate from the main health centre. This situation was perceived by the TB patients in the current study as causing stigma because once they were seen entering the department, they feared they would be labelled as HIV positive.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Another study reported a defaulter rate of 14% in Vietnam in 2004 [6] and 10% in 2014 in Lima, Peru. [7] WHO [8] reports that TB incidence has worsened in Africa especially sub-Saharan Africa where the epidemic is worsened by the HIV/AIDS pandemic. A low treatment success rate of 70% has been reported in Africa which has been blamed on treatment defaulting.…”
Section: Introductionmentioning
confidence: 99%